Guaranteed result for the differential game of two pursuers and one evader on a cylinder - P., Karapanan; Gafurjan, Ibragimov; Alias, Idham Arif; Mat Hasim, Risman (Universiti Putra Malaysia, 2021)
We study a pursuit differential game of two pursuers and one evader on a cylinder. We reduce the differential game to a differential game of two groups of countably many pursuers and one group of countably many evaders in R 2 where all the players from each group are controlled by one control parameter subjected to geometric constraint. We obtain an estimate from above for the value of the game and construct strategies for the pursuers.